INTEGRASI DISTRIBUSI DATA RADAR MENGGUNAKAN TEKNOLOGI BLOCKCHAIN DAN KRIPTOGRAF - Fahmi Rosyidi; Masbah R.T. Siregar; Abdul Multi (Institut Sains dan Teknologi Nasional, 2022)
Abstract Currently radar is widely used in various fields such as meteorology, military, police, shipping, aviation, agriculture, disaster, and research. Meanwhile, currently the use of radar is still in the form of sectoral, partial, and fragmented so that the use of radar data is only internal. With Indonesia's geographical condition which is very broad and the integration and distribution of radar data has not been maximized, this has resulted in the lack of geographic area of ​​Indonesia that is reached by radar. The use or exchange of radar data still uses client-server-based information technology, and with centralized storage which has risk factors for information security and privacy that are vulnerable to being misused or exploited. In addition, there is the possibility of data loss which makes it difficult to get data back, even when you have implemented a backup system with cloud or other protection, there is still a risk of complete data loss when compared to implementing a decentralized platform. Therefore, it is necessary to integrate and distribute radar data with a decentralized platform so that the radar data is not sectoral, partial, and fragmented. This integration and distribution of radar data will later be able to maximize the use of cross-field radar so that one radar can be used more optimally for all fields including meteorology, military, police, shipping, aviation, agriculture, disaster, and research. One technology that can be used for the integration of radar distribution is blockchain and cryptography. Blockchain and asymmetric cryptography in addition to increasing data security, can also guarantee that data entering the blockchain system comes from the correct source. The larger the bit asymmetric cryptographic key used, the more secure the data. Keywords — Radar, Blockchain, Cryptography, Integrated Distribution.